Synchronous degradation of aqueous benzotriazole and bromate reduction in catalytic ozonation: Effect of matrix factor, degradation mechanism and application strategy in water treatment - Yuting Zhang; Ji, Haodong; Liu, Wen; Zhenbei Wang; Zilong Song; Yiping Wang; Liu, Chao; Bingbing Xu; Fei Qi (Science of The Total Environment, 2020)
Ozone-based technologies are used for micro-pollutants removal in wastewater treatment. However, the generation of the toxic by-product bromate (BrO3−) is of a great concern. LaCoO3 (LCO) catalytic ozonation has been used to overcome this significant drawback in the sole ozonation, achieving better BrO3− elimination efficiency. However, a key challenge is how to enhance micro-pollutant (benzotriazole, BZA) degradation efficiency and to eliminate formed BrO3− synchronously under various water qualities in drinking water or wastewater treatment. Therefore, the objective of this study is to propose a practical strategy of BZA removal and BrO3− reduction synchronously in water or wastewater treatment. In this study, important factors influencing BZA removal and BrO3− reduction were investigated, including [catalyst], [BZA], initial pH solution, [NH4+-N] and [(bi)carbonate alkalinity]. Based on the performance and mechanism of these effects, a practical strategy for BZA degradation and BrO3− elimination with and without Br− in the influent was developed. Additionally, the density functional theory (DFT) calculation successfully predicted the attack site on BZA by molecular ozone and formed hydroxyl radical (HO·) during LCO catalytic ozonation. Fukui indexes of f+ and f0 were calculated to forecast direct ozone molecule and HO· attack, respectively. Combination of DFT calculation with intermediates that identified through liquid chromatography-quadrupole time-of-flight mass spectrometry (LC-Q-TOF-MS), BZA degradation pathway was established more accurately. Additionally, four new intermediates were identified in this study. Overall, this study proposes a useful strategy for synchronous micro-pollutants degradation and BrO3− elimination, while also suggesting the feasibility of LCO catalytic ozonation for water or wastewater purification.
Keywords: Benzotriazole; Bromate; Catalytic ozonation; Matrix factor; Theoretical computations